Dostęp do informacji publicznej – zagadka i parawan - Sobczak, Jacek (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2008)
Article 3a, introduced to press law, is of immense importance, which is underestimated in practice. In respect of the press access to public information, it makes a journalist’s rights equal with the rights of any subject who can apply for public information. The legislator, who amended the press law, failed to define the notion of‘public information’ referred to in the above-mentioned regulation.